Ecology of medical care of the ward 11 community registered to the Chiawelo Community Practice - Pillay, Santhuri (My University, 2020)
Background Community-based primary care (COPC) has been shown to be more effective than a facility based approach. Incorporating this in the National Health Insurance scheme would improve community involvement and satisfaction of services. Based on the concept of ecology of medical care, this research aimed to explore the experiences of a community exposed to the COPC approach in a facility with a defined population. Methods Cross-sectional descriptive study using a questionnaire to evaluate the utilisation of medical and alternate care in Chiawelo, Soweto. A total of 422 adults from different households in the demarcated service delivery area were evaluated. Results Key findings from this study showed a high utilisation rate of the Chiawelo Community Practice (CCP), that was largely proportional to the incidence of perceived ill-health. The service was usually used for acute complaints in the majority of instances. Specialised services at the Chiawelo Community Health Centre (CHC) were frequently used. On comparison of general satisfaction and perception of accessibility, the CCP rated much higher than the CHC. The CHW’s, associated with the CCP, either reduced or had no effect on the frequency of consultations. Despite challenges around the booking systems and cost of phoning for appointments, participants valued the services they received. Conclusion The overall experience of the sampled community was supportive of the COPC facility.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine in Family Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2020